Pac-Man Josephson junctions: useful trigonometric puzzles? - R. De Luca (Revista Brasileira de Ensino de Física, 2020)
Abstract Rather interesting trigonometric equations arise when considering a Josephson junction obtained by embedding a Pac-Man shaped superconducting island in between two superconducting electrodes. In the present work we unfold these equations, written in terms of the superconducting phase difference between the two electrodes, and find the current-phase relation and the maximum superconducting current of the Josephson junction network. The solution of the trigonometric equations defining the superconducting current state of the system can be proposed to advanced high-school students or to undergraduate students in an interdisciplinary lecture.